Sex effects across the lifespan in women with multiple sclerosis. (June 2020) - Krysko, Kristen M.; Graves, Jennifer S.; Dobson, Ruth; Altintas, Ayse; Amato, Maria Pia; Bernard, Jacqueline; Bonavita, Simona; Bove, Riley; Cavalla, Paola; Clerico, Marinella; Corona, Teresa; Doshi, Anisha; et al.
Multiple sclerosis (MS) is an autoimmune inflammatory demyelinating central nervous system disorder that is more common in women, with onset often during reproductive years. The female:male sex ratio of MS rose in several regions over the last century, suggesting a possible sex by environmental interaction increasing MS risk in women. Since many with MS are in their childbearing years, family planning, including contraceptive and disease-modifying therapy (DMT) counselling, are important aspects of MS care in women. While some DMTs are likely harmful to the developing fetus, others can be used shortly before or until pregnancy is confirmed. Overall, pregnancy decreases risk of MS relapses, whereas relapse risk may increase postpartum, although pregnancy does not appear to be harmful for long-term prognosis of MS. However, ovarian aging may contribute to disability progression in women with MS. Here, we review sex effects across the lifespan in women with MS, including the effect of sex on MS susceptibility, effects of pregnancy on MS disease activity, and management strategies around pregnancy, including risks associated with DMT use before and during pregnancy, and while breastfeeding. We also review reproductive aging and sexual dysfunction in women with MS.